2005
DOI: 10.4321/s0213-61632005000100003
|View full text |Cite
|
Sign up to set email alerts
|

The ZARADEMP Project on the incidence, prevalence and risk factors of dementia (and depression) in the elderly community: I. The context and the objectives

Abstract: Background and Objectives: The public health dimension of the problem of dementia and depression in the elderly population is well documented, but epidemiological data are generally considered to be insufficient and, at times, contradictory. This paper identifies relevant research areas for the ZARADEMP Project, which follows the Zaragoza Study (or ZARADEMP 0) and is part of both EURODEM and EURODEP Studies. Methods: Review of the literature. Hypotheses emerging in previous studies of this research group. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…Efficiency coefficients and population norms very similar to the ones reported by Folstein et al in the USA have been found in Zaragoza [22,23]. The Katz Index [28,29], which assesses the Basic Activities of Daily Living, and the IADL scale [30,31] were successfully translated and validated in Spanish.…”
Section: Covariatesmentioning
confidence: 63%
See 1 more Smart Citation
“…Efficiency coefficients and population norms very similar to the ones reported by Folstein et al in the USA have been found in Zaragoza [22,23]. The Katz Index [28,29], which assesses the Basic Activities of Daily Living, and the IADL scale [30,31] were successfully translated and validated in Spanish.…”
Section: Covariatesmentioning
confidence: 63%
“…Data collection and sample characteristics have been described elsewhere [22,23]. In short, a random sample, stratified by sex and age, of communitydwelling persons aged at least 55 years was drawn from the census list of the city of Zaragoza (Spain) in 1991.…”
Section: Samplementioning
confidence: 99%
“…Similar methods were used in both studies, but there were differences in the sampling frame due to the different objectives in both investigations. The background, objectives and general methodology of the ZARADEMP Project are described in previous articles (Lobo et al 2005a, Lobo et al 2005b. In brief, this is an epidemiological study with three waves, but only the results of Wave I (ZARADEMP I), the baseline, cross-sectional study will be used here.…”
Section: Methodsmentioning
confidence: 99%
“…Comparative studies in different time periods, which are quite limited in the inter-national literature (Kokmen et al 1993), might also test environmental hypotheses. Since we have conducted during the ZARADEMP Project, as described in a previous paper (Lobo et al 2005a), a reappraisal of the age and sex distribution of dementia in the same city, we could compare the findings with data collected in the same city the previous decade and using the same methods. We now hypothesize that, compared to ZARADEMP 0, a decreased prevalence of GMS-AGECAT "organic brain syndrome" in men will be found in ZARADEMP I, particularly in the age groups between 70 years and 84 years.…”
Section: Introductionmentioning
confidence: 99%
“…A number of neuropsychological and behavioral predictors of dementia have been identified, including for example, older age, impairment in immediate and delayed recall, and functional disability. 2,11 Classifications that include and are associated with these predictors would be expected to identify individuals at higher risk of progression. The concept of MCI as defined by the Mayo Clinic is an amnestic subtype, which in clinic-based samples represents a greater risk of developing dementia, most often AD, 2,12 although whether this condition is distinct from early AD has been questioned, 13 and there is growing evidence that this and related classifications are unstable in population-based studies.…”
mentioning
confidence: 99%